T cell receptor antagonism interferes with MHC clustering and integrin patterning during immunological synapse formation - Sumen, Cenk (The Rockefeller University Press, 2004)
T cell activation by nonself peptide–major histocompatibility complex (MHC) antigenic complexes can be blocked by particular sequence variants in a process termed T cell receptor antagonism. The inhibition mechanism is not understood, although such variants are encountered in viral infections and may aid immune evasion. Here, we study the effect of antagonist peptides on immunological synapse formation by T cells. This cellular communication process features early integrin engagement and T cell motility arrest, referred to as the “stop signal.” We find that synapses formed on membranes presenting antagonist–agonist complexes display reduced MHC density, which leads to reduced T cell proliferation that is not overcome by the costimulatory ligands CD48 and B7-1. Most T cells fail to arrest and crawl slowly with a dense ICAM-1 crescent at the leading edge. Similar aberrant patterns of LFA-1/ICAM-1 engagement in live T–B couples correlate with reduced calcium flux and IL-2 secretion. Hence, antagonist peptides selectively disable MHC clustering and the stop signal, whereas LFA-1 valency up-regulation occurs normally.